1984
DOI: 10.1287/opre.32.6.1195
|View full text |Cite
|
Sign up to set email alerts
|

A Cutting Plane Algorithm for the Linear Ordering Problem

Abstract: The linear ordering problem is an NP-hard combinatorial optimization problem with a large number of applications (including triangulation of input-output matrices, archaeological senation, minimizing total weighted completion time in one-machine scheduling, and aggregation of individual preferences). In a former paper, we have investigated the facet structure of the 0/1-polytope associated with the linear ordering problem. Here we report on a new algorithm that is based on these theoretical results. The main p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
161
0
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(164 citation statements)
references
References 10 publications
1
161
0
2
Order By: Relevance
“…This is a well-known set of instances, first used in [18]. It contains 50 real-world linear ordering problems taken from input-output tables from various sources.…”
Section: Input/output Matricesmentioning
confidence: 99%
“…This is a well-known set of instances, first used in [18]. It contains 50 real-world linear ordering problems taken from input-output tables from various sources.…”
Section: Input/output Matricesmentioning
confidence: 99%
“…However, it has been shown that this problem has 2 n       equations, n(n-1) nonnegativity constraints, 2 3 n       3-dicycle inequalities, 120 6 n       3-fence inequalities, and 360 6 n       Möbius ladder inequalities [6]. Due to this enormous number of constraints, it is impractical to list all the constraints and solve the linear program using available computer code.…”
Section: Branch and Cut Algorithmmentioning
confidence: 99%
“…The following heuristic was described by Reinelt [6]. The heuristic is based on the uniqueness of the solution in Figure 1 for any 3-fence.…”
Section: Heuristic:[5]mentioning
confidence: 99%
“…The Linear Ordering Problem(LOP) has numerous applications in economics, archaeology, scheduling, the social sciences, and aggregation of individual preferences [5,6,7,8]. Of all these applications, the most famous one may be "the Triangulation for Input-Output Matrices" [7], which measures the movement of goods from one "sector" to another in economics research.…”
Section: Introductionmentioning
confidence: 99%
“…Grotschel et al first proposed a cutting plane algorithm in [6,7]; Mitchell and Borchers [8] improved the result by combining the cutting plane with the interior point algorithm. However, all of these exact algorithms are extremely time-consuming.…”
Section: Introductionmentioning
confidence: 99%